2023
DOI: 10.1371/journal.pone.0282044
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use electronic medical record (EMR) system and its associated factors among health professionals working in Amhara region Private Hospitals 2021, Ethiopia

Abstract: Introduction Despite the high expectations of electronic medical records as a great prospect for improving performance in healthcare, the level of adoption and utilization, particularly in a developing country, is low. Knowing the willingness to use the electronic medical record system in the private hospital has an impact on the future implementation status and utilization of the electronic medical record in Ethiopia. However, there was no evidence of the status of the willingness to use electronic medical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(31 reference statements)
1
0
0
Order By: Relevance
“…On the other hand, we found that time constraints imposed by workload, the inability to locate information quickly, and an abundance of clinically irrelevant information were the main obstacles to using electronic health information resources in daily practice. This result is compatible with a study conducted in Ethiopia, which revealed that the majority of healthcare professionals experienced difficulties when utilizing EHIRs, such as inadequate computer skills, a lack of computer training, and limited familiarity with the electronic medical record system ( Senishaw et al, 2023 ). Furthermore, technical challenges such as system compatibility issues and user interface complexity can impede health professionals' acceptance and proficiency in using EHIR systems ( Dharmawan et al, 2022 , Garavand et al, 2016 , Rahal et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, we found that time constraints imposed by workload, the inability to locate information quickly, and an abundance of clinically irrelevant information were the main obstacles to using electronic health information resources in daily practice. This result is compatible with a study conducted in Ethiopia, which revealed that the majority of healthcare professionals experienced difficulties when utilizing EHIRs, such as inadequate computer skills, a lack of computer training, and limited familiarity with the electronic medical record system ( Senishaw et al, 2023 ). Furthermore, technical challenges such as system compatibility issues and user interface complexity can impede health professionals' acceptance and proficiency in using EHIR systems ( Dharmawan et al, 2022 , Garavand et al, 2016 , Rahal et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%